Arthritis glove provision in rheumatoid arthritis and hand osteoarthritis: A survey of United Kingdom rheumatology occupational therapists. (March 2022) - Hammond, Alison; Prior, Yeliz
Introduction: Hand pain and function limitations are common in rheumatoid arthritis (RA) and hand osteoarthritis (HOA). Provision of arthritis (compression) gloves to relieve hand symptoms is increasing in occupational therapy. Research evaluating arthritis gloves dates to the 1990s, focussing on night-wear of full-length finger gloves in RA. This survey examined glove provision in contemporary clinical practice in the United Kingdom. Methods: A survey of arthritis glove provision in RA was conducted with Royal College of Occupational Therapists Rheumatology Specialist Section members. A more detailed survey about glove provision in RA and HOA was conducted with rheumatology occupational therapists in North-West England. Results: Response rates were good, with 60 (73%) therapists responding to the national and 24 (69%) to the regional surveys. Most therapists provided open-finger gloves (commonly Isotoner TM ) to about a third of their RA and HOA patients, and to those with any arthritic condition causing significant hand pain and/or swelling. Day-wear was as common as night-wear, and patients were advised to wear these 'as and when' for hand symptom relief and support for hand function. They were advised not to wear gloves continually in the day, and regularly perform hand exercises and monitor for potential adverse effects, for example, skin discolouration. Therapists commonly provide replacement gloves as these are often used long-term. Conclusion: Prescription of arthritis gloves has changed considerably in the last 30 years, with open-finger gloves provided to a wider range of people with arthritis, for a broader range of clinical reasons.